The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1111/j.1368-5031.2006.00682.x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus and stroke

Abstract: The aim of this article was to describe (i) the epidemiology and outcomes of stroke relating to diabetes; (ii) the pathophysiology of diabetes as a risk factor for stroke; (iii) the management of acute stroke in patients with diabetes; (iv) the evidence of primary and secondary prevention of stroke in patients with diabetes; and (v) the risk of new-onset diabetes using older antihypertensive agents. The combination of diabetes and stroke disease is a major cause of morbidity and mortality worldwide. Evidence f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
71
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 92 publications
4
71
0
5
Order By: Relevance
“…Under these conditions of injured vasculature, cold temperature could more seriously affect patients with hyperglycemia. 34 The reason why the effect of hyperglycemia was limited to stroke is still unclear. A cohort study of male Japanese workers found that smoking, even at a low level, increased the risk of cardiovascular death.…”
Section: Discussionmentioning
confidence: 99%
“…Under these conditions of injured vasculature, cold temperature could more seriously affect patients with hyperglycemia. 34 The reason why the effect of hyperglycemia was limited to stroke is still unclear. A cohort study of male Japanese workers found that smoking, even at a low level, increased the risk of cardiovascular death.…”
Section: Discussionmentioning
confidence: 99%
“…Associated dyslipidemia and hypertension also probably contribute (40). Endothelial proliferation and thickening of the basement membrane in small blood vessels lead to increased risk of lacunar infarction (41,42). Increased coagulability and platelet aggregability as well as decreased fibrinolysis in diabetic patients may augment the risk of large-artery infarction (40).…”
Section: Discussionmentioning
confidence: 99%
“…People with diabetes have a particularly high risk of mortality and morbidity from coronary heart disease and stroke (2,3). Moreover, diabetes has been the seventh leading cause of death, and the agestandardized mortality rate for diabetes has increased by 45% from 1987 to 2002 in the U.S. (4).…”
mentioning
confidence: 99%